Kinetics and Mechanism of Oxidation of Ascorbic Acid by Ruthenium(III) - TRIPATHI, P.P.; MEHROTRA, R.M. (Asian Journal of Chemistry, 2010)
Oxidation of ascorbic acid (AH2) by ruthenium(lII) has been investigated kinetically in acidic medium, which indicated a first order dependence with respect to ascorbic acid and ruthenium(III) and an inverse order dependence with respect to hydrogen ion concentration. An insignificant effect on the reaction rate was observed with a change in ionic strength. Energy of activation and entropy of activation have been calculated and an appropriate mechanism consistent with the experimental data has also been formulated.